2021
DOI: 10.1038/s41467-021-25923-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetopause ripples going against the flow form azimuthally stationary surface waves

Abstract: Surface waves process the turbulent disturbances which drive dynamics in many space, astrophysical and laboratory plasma systems, with the outer boundary of Earth’s magnetosphere, the magnetopause, providing an accessible environment to study them. Like waves on water, magnetopause surface waves are thought to travel in the direction of the driving solar wind, hence a paradigm in global magnetospheric dynamics of tailward propagation has been well-established. Here we show through multi-spacecraft observations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…The phase of the compressional magnetic field reverses either side of the boundary, that is, when the magnetosphere is compressed the magnetosheath becomes rarefied. Archer et al (2021), A21 herein, found similar motion of the subsolar bow shock, lagging behind the magnetopause. While the magnetopause waves travel tailward at the equatorial flanks, between 09 and 15 hr Magnetic Local Time (MLT) they are stationary despite significant magnetosheath flows being present.…”
Section: Surface Modessupporting
confidence: 61%
See 1 more Smart Citation
“…The phase of the compressional magnetic field reverses either side of the boundary, that is, when the magnetosphere is compressed the magnetosheath becomes rarefied. Archer et al (2021), A21 herein, found similar motion of the subsolar bow shock, lagging behind the magnetopause. While the magnetopause waves travel tailward at the equatorial flanks, between 09 and 15 hr Magnetic Local Time (MLT) they are stationary despite significant magnetosheath flows being present.…”
Section: Surface Modessupporting
confidence: 61%
“…Archer et al. ( 2021 ), A21 herein, found similar motion of the subsolar bow shock, lagging behind the magnetopause. While the magnetopause waves travel tailward at the equatorial flanks, between 09 and 15 hr Magnetic Local Time (MLT) they are stationary despite significant magnetosheath flows being present.…”
Section: Introductionmentioning
confidence: 54%
“…It has been shown that jets appear more frequently behind the Qpar shock rather than the Qperp one (Raptis, Aminalragia‐Giamini, et al., 2020; Raptis, Karlsson, et al., 2020; Vuorinen et al., 2019), and typically have significant effects on the geomagnetic environment of Earth (Plaschke et al., 2018). For example, they can enhance or initiate magnetopause reconnection (Escoubet et al., 2020; Hietala et al., 2018; Ng et al., 2021; Vuorinen et al., 2021), accelerate particles (Liu et al., 2019, 2020), generate a variety of different waves in the MSH and outer magnetosphere environment (Archer et al., 2019, 2021; Katsavrias et al., 2021) and even have effects on the inner magnetosphere and ionosphere (Hietala et al., 2012; Norenius et al., 2021; Wang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…outer magnetosphere environment (Archer et al, 2019(Archer et al, , 2021Katsavrias et al, 2021) and even have effects on the inner magnetosphere and ionosphere (Hietala et al, 2012;Norenius et al, 2021;Wang et al, 2018).…”
mentioning
confidence: 99%
“…ULF waves in the magnetosphere are studied using coupled global magnetospheric models (e.g., Claudepierre et al, 2008;Hartinger et al, 2014;Claudepierre et al, 2016;Komar et al, 2017) and in simplified field geometries to isolate and better understand underlying physics (Xia et al, 2017;Denton, 2018;Elsden and Wright, 2020;Lysak et al, 2020). Examples of simulations of ULF waves in the magnetosphere presented at GEM UMEA sessions include studies of: global magnetospheric ULF wave modes (Claudepierre et al, 2010;Elsden et al, 2016;Wright, 2017, 2020;Xia et al, 2017;Lysak et al, 2020), magnetospheric ULF wave propagation (Degeling et al, 2018), growth and propagation of EMIC waves (Denton et al, 2014), magnetopause surface waves (Lin et al, 2017;Archer et al, 2021), and interaction of ULF waves with ring current and radiation belt particle populations (Komar et al, 2017;Denton et al, 2019;Patel et al, 2019).…”
Section: Ulf Wave Modeling and The Gem Ulf Wave Modeling Challengementioning
confidence: 99%